Argentina : Fourth Review under the Stand-By Arrangement, Request for Waivers of Applicability and Modification of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Argentina's Fourth Review of the Stand-By Arrangement, Request for a Waivers of Applicability and Modification of Performance Criteria, and Financing Assurances Review. The report highlights that with very high inflation and an increase in gross financing needs in coming months, discussions centered on how best to mitigate risks to the program, bolster market confidence, and calibrate monetary policy to continue bringing down inflation. The authorities have revamped their debt management strategy to support higher rollovers and an extension of average maturity of new issuance to the degree permitted by market conditions. The authorities have maintained a cautious approach to expenditure authorization in order to safeguard their program's fiscal targets. The Argentine authorities' efforts to increase rollover rates on public debt and to lengthen the maturity of new debt issuance should help mitigate financing risks in the period ahead. Ongoing efforts to improve the functioning of local sovereign debt markets will help improve market liquidity and lower financing costs.